SMILE Application-Excursion to Space to Improve the Critical Thinking Skills of Fourth Grade Elementary School Students - Arsy, Nabila; Hanif, Muhammad (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The low interest of students in learning is due to the need for more interactive learning media in line with technological developments in the 21st century. This research aims to create an application-based learning media called SMILE (Smart Interactive Learning) - Excursions to Space, which can improve the critical thinking skills of grade VI students on solar system material. This research uses the ADDIE teaching material development model, which consists of 5 stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques were carried out by interview, expert and student validation, and evaluation questions (pretest and post-test). Data analysis techniques include data on the learning media development process, data on the feasibility of learning media through expert validation and user validation, and data on the effectiveness of teaching media with the T-test and N-Gain test. The results showed that the SMILE application learning media received the "Very Feasible" category from material experts, media experts, and students (users). The results also showed increased students' critical thinking skills after learning the SMILE application, which was proven by the T-test and N-Gain test results in the "high" category. This research concludes that an application-based learning media that is feasible and effective for improving students' critical thinking skills is produced.